Quinolizidine Alkaloid Biosynthesis in Lupins and Prospects for Grain Quality Improvement - Frick, Karen M.; Kamphuis, Lars G.; Siddique, Kadambot H. M.; Singh, Karam B.; Foley, Rhonda C. (Frontiers in Plant Science, 2017)
Quinolizidine alkaloids (QAs) are toxic secondary metabolites found within the genus Lupinus, some species of which are commercially important grain legume crops including L. angustifolius (narrow-leafed lupin), L. luteus (yellow lupin), L. albus (white lupin) and L. mutabilis (pearl lupin), with narrow-leafed lupin (NLL) grain being the most largely produced of the four species in Australia and worldwide. While QAs offer the plants protection against insect pests, the accumulation of QAs in lupin grain complicates its use for food purposes as QA levels must remain below the industry threshold (0.02%), which is often exceeded. It is not well understood what factors cause grain QA levels to exceed this threshold. Much of the early work on QA biosynthesis began in the 1970-1980s, with many QA chemical structures well-characterized and lupin cell cultures and enzyme assays employed to identify some biosynthetic enzymes and pathway intermediates. More recently, two genes associated with these enzymes have been characterized, however the QA biosynthetic pathway remains only partially elucidated. Here, we review the research accomplished thus far concerning QAs in lupin and consider some possibilities for further elucidation and manipulation of the QA pathway in lupin crops, drawing on examples from model alkaloid species. One breeding strategy for lupin is to produce plants with high QAs in vegetative tissues while low in the grain in order to confer insect resistance to plants while keeping grain QA levels within industry regulations. With the knowledge achieved on alkaloid biosynthesis in other plant species in recent years, and the recent development of genomic and transcriptomic resources for NLL, there is considerable scope to facilitate advances in our knowledge of QAs, leading to the production of improved lupin crops.